The influence of motivation and career opportunities on career choice: the mediating role of psychological capital - Purwanto (Prodi Magister Ekonomi Syariah FEBI UIN Walisongo Semarang, 2025)
The rapid transformation brought by the industrial revolution 4.0 has created new challenges for the Indonesian workforce, particularly in aligning motivation, career opportunities, and psychological capital in career decision-making. This study aims to explain the causal relationship between motivation, career opportunities, psychological capital, and career choice among final-year students and recent graduates in Semarang City. Using a quantitative explanatory approach, data were collected from 142 respondents through purposive sampling and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that motivation and career opportunities significantly influence career choice both directly and indirectly through psychological capital as a mediating variable. Motivation and perceived opportunities positively affect psychological capital, which in turn strengthens individuals’ confidence, optimism, hope, and resilience in making career decisions. The model explains 61.1% of the variance in career choice, confirming that psychological capital functions as a key mediating mechanism linking internal motivation and external opportunities. These findings contribute to human resource management and positive psychology by highlighting the importance of integrating psychological development into career planning strategies, suggesting that educational institutions and policymakers should foster motivation and psychological capital to enhance workforce readiness and career sustainability.